Ultrasonic Velocity and Apparent Molar Compressibility of Trichloroacetic Acid in Aqueous Ethanol. - NlKAM, P.S.; HASAN, MEHDI (Asian Journal of Chemistry, 2010)
Ultrasonic velocities of solutions of trichloroacetic acid in aqueous ethanol have been measured at 25, 30, 35 and 40ºC, using a single crystal interferometer at frequency of 1.5 MHz. The ultrasonic velocity (U), density (ρ) and concentration (C) are used to calculate adiabatic compressibility (βad), intermolecular free length (Lf) and apparent molar compressibility (φk). Bachem's relation and Gucker's limiting law have been found to obey and constants A, B and and Sk of these relations in various solvents have also been reported.